Boosting interfacial charge migration of TiO2/BiVO4 photoanode by W doping for photoelectrochemical water splitting. (20th March 2019) - Jia, Yulong; Wang, Zhonghao; Ma, Ying; Liu, Jiali; Shi, Wenbing; Lin, Yinhe; Hu, Xun; Zhang, Kan
Abstract: Heterojunction electrode requires thermodynamically favored band edge energetics to boost charge separation for efficient photoelectrochemical (PEC) water splitting. In this study, we report that TiO2 nanorods (NRs) doped with W, formed by solid state diffusion, can tune the band structure to construct a Type II staggered heterojunction with BiVO4 . The W-TiO2 /BiVO4 heterojunction overcomes the intrinsic energy barrier between BiVO4 and TiO2 NRs by downward shifting of conduction band position, exhibiting 4-times higher PEC performance (2.5 mA/cm 2 ) than TiO2 /BiVO4 . Moreover, the photocurrent characteristics and photon-to-current conversion efficiency (IPCE) indicate that the W-TiO2 /BiVO4 heterojunction retains the small onset potential of TiO2 and light harvesting capability of BiVO4 . Especially, compared to popular WO3 /BiVO4 heterojunction, the W-TiO2 /BiVO4 heterojunction can present better stability towards long-term solar water splitting due to the compatibility of pH sensitivity. This study can shed a new insight on design of heterojunction by regulating band edge energetics for PEC water splitting. Graphical abstract: Image 1